Determination and Detoxification of Aflatoxins in Cattle Feed Samples Collected from Local Areas of Lahore, Pakistan - Naeem, Hafiza Akifa; Ashraf, Aqeela; Rafi, Uzma; Zahra, Naseem (BioScientific Review, 2023)
Aflatoxins are naturally occurring toxic metabolites produced by fungi in various food crops. The current study aims to determine the level of aflatoxins by using thin-layer chromatography in cattle feed samples and evaluates different methods including physical, chemical, and biological methods used for detoxification. A total of 80 samples including 40 fresh feed samples (20 wanda and 20 makai) and 40 dry feed samples (10 samples of dana, 10 samples of chokhar, 10 samples of toori, 3 samples of Khal, and 7 samples of makai dana) were collected from 22 areas of Lahore, Pakistan. Physical methods used for detoxification included washing and boiling, while chemical methods included detoxification with 10% citric acid, 10% acetic acid, 2% sodium hydroxide, and 2% hydrochloric acid. Finally, biological methods included detoxification with 0.15% mustard oil and 0.15% black seed oil. Among the samples, 9 wanda, 7 makai, 3 khal, 2 dana, and 2 chokhar samples were found to be contaminated. Only 6.25% of the samples exceeded the permissible limit of 20 parts per billion (ppb) set by the USFDA. A chemical method applied to khal samples achieved the highest reduction percentage at 63.64%. Meanwhile, physical and biological methods resulted in reduction percentages of 23.91% and 35.72%, respectively. These findings demonstrate the efficacy of various approaches, particularly highlighting the significant reduction achieved with the chemical method in khal samples. Moreover, these findings contribute to the understanding of effective strategies for mitigating aflatoxin contamination in cattle feed.